Incidence of chemotherapy discontinuation and characteristics of elderly patients with non-small cell lung cancer treated with platinum-based doublets - Alexa, Teodora; Lavinia, Anti; Luca, Andrei; Miron, Lucian; Alexa, Ioana Dana (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : To compare patient’s characteristics, clinical data, and rates of chemotherapy discontinuation in advanced NSCLC (non-small cell lung cancer) patients treated with platinum-based association chemotherapy (elderly vs. younger counterparts). To evaluate if there are certain factors that can predict discontinuation of chemotherapy. Material and methods : A retrospective analysis of all cases of advanced NSCLC treated with either cisplatin-gemcitabine or cisplatin-vinorelbine at the Regional Institute of Oncology Iaşi between January 2012 and December 2013 was performed. Patients were divided into two groups: over 70 years old and under 70 years old. Patient’s characteristics and clinical data (including whether or not the patient discontinued treatment) were recorded for each case. Results : The elderly patients had more comorbidities (p = 0.003), were prescribed a larger number of pills (p = 0.02), and had longer periods of hospitalisation (p = 0.005). No difference in toxicity was noted between the two groups. Five patients chose to discontinue chemotherapy in the elderly group. Only two patients made the same choice (p = 0.02) in the younger group. Correlation analysis revealed that refusal of further chemotherapy was associated with the length of hospital stay, number of pills per day, and smoking status. Conclusions : Geriatricians should minimise iatrogeny and polypharmacy by optimising long-term treatment. This will increase the chance that elderly patients will not discontinue chemotherapy. Hospital stay should be reduced to a minimum. As life span increases so does the number of elderly patients with cancer; it is vital to understand and prevent the causes of chemotherapy discontinuation in order to achieve optimal therapeutic results.